18x^2 + 2x + y^2 = 1
<span>==> 18(x^2 + x/9) + y^2 = 1 </span>
<span>==> 18(x^2 + x/9 + 1/324) + y^2 = 1 + 1/18 </span>
<span>==> 18(x + 1/18)^2 + y^2 = 19/18 </span>
<span>==> (x + 1/18)^2/19 + (y - 0)^2/(19/18) = 1. </span>
<span>By comparing this to the standard form of an ellipse, the center is at (-1/18, 0). </span>
The equation would be 60h=m
Answer:
commutative property of multiplication
Step-by-step explanation:
examples of this property:
xy=yx
1*3=3*1=3
6*9=9*6=54
Answer:
17C5+11C5
Step-by-step explanation:
Well there are 17 and chooses 5 that's 17C5
there are 11 men abd chooses 5 that's 11C5
so add them up
17C5+11C5